Carboxymethyl-cellulase and filter-paperase activities of napier grass fermentation by new bacterial isolates - Manap, Shahirah; Wan Omar, Wan Siti Atikah; Saad, Wan Zuhainis; Harith, Siti Suhaila; Mohd Noor, Badrul Hisham; Mohd Mydin, Marlina; Kamarullah, Shahida Hanum; Mohamad, Rosfarizan (2014)
Cellulosic biomass is a renewable and most abundant resource with high potential for bioconversion to biofuels. It can be degraded by cellulase produced by cellulolytic producing bacteria. Proximately, three different types of cellulase needed for effective enzymatic hydrolysis; endoglucanase (CMCase), exocellobiohydrolase and β -glucosidase. Total cellulase activity can be determined by measuring reducing sugar derived from filter paper (FPase) while endoglucanase (CMCase) can be determined by measure reducing sugar release from carboxymethyl- cellulose (CMC). In this study, the CMCase and FPase activities of new six isolates from different environments (compost: C5/1 and C5/2; ponds: L5/1, L6/2, and L6/5; and decayed wood: D6/1) were examined according methods recommended by the International Union of Pure and Applied Chemistry (IUPAC).The fermentation has been conducted for 4 days incubation period at 37°C and agitated at 150 rpm. Napier grass has been used as a substrate. As a result, the C5/2 exhibited the highest enzymes activities of CMCase and FPase, which were 2.205U/mL and 0.39U/mL, respectively.